Pendidikan Kemaritiman Model EJoy-ME Berbasis Potensi Lokal Ekosistem Mangrove Lantebung - Hayati, Riza Sativani; Ma’rifah, Destri Ratna (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
Maritime education is very important for students because it provides a comprehensive understanding of the sea and its resources, fosters a love for the sea, and improves responsible behavior towards marine conservation. South Sulawesi has high biodiversity, there is the Lantebung Mangrove ecosystem which represents the diversity of mangrove ecosystems in Makassar. This study aims to 1) conduct a study on the potential of the Lantebung Mangrove ecosystem for the development of maritime education learning resources and 2) apply the Experiential and Joyful Learning-Marine Edutourism (EJoy-ME) learning model based on the potential of the Lantebung Tourism Village Mangrove ecosystem to improve students' marine literacy. The method used is observation of the potential of the Lantebung Mangrove ecosystem natural resources and quasi-experimental EJoy-ME learning model. The results of the study indicate that the Lantebung Mangrove ecosystem has the potential to be developed as a learning resource for maritime education through EJoy-ME. The application of EJoy-ME has been proven to be able to improve students' marine literacy. The EJoy-ME learning model also received a positive response from students, namely satisfaction with the learning process and providing a pleasant learning experience.